The Utilization of Hindhu Buddhist Heritage Sites to Develop The Student’s Historical Literacy of Public Senior High School 1 Boja - Suminar, Retno; Wasino, Wasino; Handoyo, Eko (Universitas Negeri Semarang, 2019)
Every citizen in Indonesia has national obligations and love for the motherland. Globalization and the rapid development of science and technology have caused the patriotism and nationalism of citizen to fade away. History has an essential function in fostering patriotism and nationalism. Public Senior High School 1 Boja has a particular problem, that is the lack of Student’s literacy skills, especially in history learning. The purpose of this research is to analyze the planning, learning process, evaluation, and obstacles of the utilization of Hindhu-Buddhist heritage in Boja region as an effort to develop students' historical literacy. This study used a qualitative method. The subjects of the research were students of Public Senior High School 1 Boja. Data collection was conducted by observation, interviews, questionnaires, and documentation. An interactive data analysis analyzed the data of the research. The results of the study were stated as follows; learning planning in developing students' historical literacy by using Hindhu-Buddhist heritage of Boja region had been illustrated in the lesson plans that teachers made, students' understanding was built based on accurate historical evidence and historical learning became more meaningful because it turned from a memorizing paradigm of historical facts to historical literacy improvement. The obstacle faced in this research was the lack of time allocation. This research concluded that the utilization of Hindhu-Buddhist heritage sites in Boja region for history learning could stimulate the students of Public Senior High School 1 Boja to develop their historical literacy.